PENGEMBANGAN KEMAMPUAN BAWASLU PEKANBARU MENERIMA PENGADUAN MASYARAKAT TERKAIT PELANGGARAN PEMILU MELALUI APLIKASI ONLINE - adlin (Universitas Serang Raya, 2024)
This service is intended to assist and develop the capacity of the Pekanbaru City Election Supervisory Board in supervising the implementation of the general election so that it runs honestly and fairly. One of the obstacles was identified in monitoring is the lack of public participation in reporting election violations. This is thought to be due to the unavailability of easily accessible reporting media. Regarding these problems, this service team was created and submitted a prototype of an application for reporting election violations to Pekanbaru Bawaslu. This application can be accessed easily by the public and through this application the report as soon as it is sent can be immediately known by the Pekanbaru Bawaslu admin. This service is carried out by: 1) Making a prototype of a violation report application to Pekanbaru Bawaslu; 2) Disseminate the use of the Application to Pekanbaru Bawaslu and others; 3) Simulating the use of the Election Violation reporting application.